1) Arrange both the polynomial is same order of exponent . It would be good to have terms arrange from highest exponent to lowest exponent i.e
For example
S(x) = x2 + 5x3 + 1 +10x
P(x) = x3 + x2 + 5 +10x

Arranging them as per suggestion above

S(x) = 5x3 +x2+ 10x +1
P(x) = x3 + x2 + 10x +5

2) Add the like term . By like term ,we mean same exponent terms. There are two method to add like terms. We either can group them horizontally and add it. We can add vertically
Horizontally
S(x) + P(x)
=x2 + 5x3 + 1 +10x + (x3 + x2 + 5 +10x)
Arranging both the polynomial in same order
=5x3 +x2+ 10x +1 + (x3 + x2 + 10x +5 )
Opening the parentthesis and grouping the like terms. In addition,no sign are changed when parentthesis are opened
= 5x3 + x3 + x2+x2 + 10x +10x + 1+5
=6x3+2x2+20x+6

Vertically
S(x) = x2 + 5x3 + 1 +10x
P(x) = x3 + x2 + 5 +10x

Arranging both the polynomial in same order

S(x) = 5x3 +x2+ 10x +1
P(x) = x3 + x2 + 10x +5

Similarly we can add three or more polynomials

Example-1
(2x3 - x+1+x2) + (x3 + 6x - 7) + (-3x2 - 11 + 2x)
Arranging them in same order
=(2x3 + x2 - x+1) + (x3 + 6x - 7) + (-3x2 + 2x - 11)

Opening the parentthesis and grouping the like terms
=2x3+x3 +x2-3x2 -x +6x+2x +1-7-11
=3x3-2x2+7x-16

## Subtracting polynomials

We many times need to subtract the two polynomial .It is very similar to adding polynomails only.Subtracting polynomials just means Subtracting the like terms.We need to follow below steps for Subtraction of polynomial
1) Arrange both the polynomial is same order of exponent . It would be good to have terms arrange from highest exponent to lowest exponent i.e
For example
S(x) = x2 + 5x3 + 1 +10x
P(x) = x3 + x2 + 5 +10x

Arranging them as per suggestion above

S(x) = 5x3 +x2+ 10x +1
P(x) = x3 + x2 + 10x +5

2) Subtract the like term . By like term ,we mean same exponent terms. There are two method to subtract like terms. We either can group them horizontally and subtract it. We can add vertically
Horizontally
S(x) - P(x)
=x2 + 5x3 + 1 +10x - (x3 + x2 + 5 +10x)
Arranging both the polynomial in same order
=5x3 +x2+ 10x +1 -(x3 + x2 + 10x +5 )
Opening the parentthesis and grouping the like terms. In Subtract, sign are reversed when parentthesis are opened i.e + becomes - and - becomes +
= 5x3 - x3 + x2 - x2 + 10x -10x + 1-5
Subtact the like term
=4x3 - 4

Vertically
S(x) = x2 + 5x3 + 1 +10x
P(x) = x3 + x2 + 5 +10x

Arranging both the polynomial in same order

S(x) = 5x3 +x2+ 10x +1
P(x) = x3 + x2 + 10x +5

Similarly we can add three or more polynomials

Example-1
(2x3 - x+1+x2) - (x3 + 6x - 7) - (-3x2 - 11 + 2x)
Arranging them in same order
=(2x3 + x2 - x+1) - (x3 + 6x - 7) - (-3x2 + 2x - 11)

Opening the parentthesis and grouping the like terms
=2x3- x3 +x2+3x2 -x -6x-2x +1+7+11
=x3+4x2-9x+18